Development, integrative study and research prospects of Deschampsia antarctica collection - Kunakh, Viktor; Twardovska, Maryana; Andreev, Igor; Drobyk, Nadia; Navrotska, Daria; Nuzhyna, Nataliia; Poronnik, Oksana; Konvalyuk, Iryna; Myryuta, Ganna; Ivannikov, Roman; et al. (Polish Polar Research, 2023)
This review presents the results of multi-year efforts for the development and integral investigation of the collection of Deschampsia antarctica É. Desv. plants originated from the maritime Antarctic. To create the collection, we have optimized the procedures and conditions for germination of seeds and generation of aseptic plants in vitro together with their subsequent clonal propagation, long-term in vitro culture, and acclimatization of plants to pot culture, and finally produced fertile plants able to set viable seeds. The collection of plants cultivated in vitro and in pots is consisted of clones of 22 different genotypes originated from eight island populations from the Argentine Islands – Kyiv Peninsula region. Some of these clones have been successfully cultured for more than ten years and were found to be genetically stable over this period. The collection was shown to be heterogeneous in a number of variables. The morphological and anatomical characteristics of the plants, as well as the data of karyological, molecular cytogenetic, molecular genetics, and biochemical analysis are presented. The created collection of D. antarctica plants can provide a valuable plant material with well-studied characteristics grown under controlled conditions to perform experimental research on the mechanisms for plant adaptation and resistance to various abiotic factors of Antarctic environment. Furthermore, development of the collection and its comprehensive characterization form the basis for further biotechnological developments focused on the use of this Antarctic plant as a source of biologically active substances, which can potentially be used for therapeutic and prophylactic purposes.